Rapid generation of secondary fibroblasts through teratoma formation - Sang Mi Cho; Jung Sun Park; Byungkuk Min; Sujin Kwon; Yong-Kook Kang (BioTechniques)
The use of secondary or reprogrammable cells in the production of induced pluripotent stem cells (iPSCs) circumvents random infection by various viral particles and random, uncontrollable integrations of the viral genomes into different genomic loci. We have developed a convenient method for repeatedly producing genetically identical secondary fibroblasts via teratoma formation using pre-existing iPSCs. The iPSCs used in this study carried doxycycline (Dox)-inducible transgenes for four transcription factors in their genome. Teratoma-derived primary cells (TOFs) were obtained in a huge amount during the culture of teratomas and showed good ability to form iPSCs similar to that of regular secondary fibroblasts. Immunohistochemistry analysis demonstrated the potential of TOF-derived iPSCs to differentiate into all three germ layers. The gene expression profiles of these TOFs and their iPSCs closely mimicked those of regular embryonic fibroblasts and embryonic stem cells/iPSCs, respectively. The possibility that the iPSCs were derived from a small part of pluripotent cells lurking in the TOF population was precluded by the observation of doxycycline-dependent and PluriSin (a compound selectively eliminating pluripotent cells)- independent formations of iPSCs. Our results showed that the TOFs retained the capability to mediate cellular reprogramming, similar to that of regular secondary fibroblasts.